2020
DOI: 10.1007/s00259-019-04677-x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging glioma biology: spatial comparison of amino acid PET, amide proton transfer, and perfusion-weighted MRI in newly diagnosed gliomas

Abstract: Purpose Imaging glioma biology holds great promise to unravel the complex nature of these tumors. Besides well-established imaging techniques such O-(2-[18F]fluoroethyl)-L-tyrosine (FET)-PET and dynamic susceptibility contrast (DSC) perfusion imaging, amide proton transfer-weighted (APTw) imaging has emerged as a promising novel MR technique. In this study, we aimed to better understand the relation between these imaging biomarkers and how well they capture cellularity and vascularity in newly diagnosed glioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…They did not report on this imaging combination for any other tumor subtypes. In another study of 46 newly diagnosed gliomas, Schon et al [ 60 ] found the tumor volume to be larger by FET PET than by DSC PWI. For identifying cellularity, FET PET parameters performed the strongest, while for vascularity, both DSC PWI and FET PET performed well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They did not report on this imaging combination for any other tumor subtypes. In another study of 46 newly diagnosed gliomas, Schon et al [ 60 ] found the tumor volume to be larger by FET PET than by DSC PWI. For identifying cellularity, FET PET parameters performed the strongest, while for vascularity, both DSC PWI and FET PET performed well.…”
Section: Resultsmentioning
confidence: 99%
“…Even in low-grade gliomas, a similar trend was observed for the two imaging modalities (P = 0:085 for APTw and P = 0:045 for CBV). Reproduced with permission from Figure 2 of Schon et al [60]. 14 Molecular Imaging this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Several analyses correlated [ 18 F]FET PET parameters with PWI-derived parameters like rCBV [19][20][21][22]. However, there is a general consensus that [ 18 F]FET uptake, especially at 20-40 min, is dominated by the expression of amino acid transporters [10,19], explaining why hotspot locations on [ 18 F]FET PET and PWI do often not coincide [22].…”
Section: Introductionmentioning
confidence: 99%
“…Data from initial studies revealed incongruent results, suggesting FET, DWI, and CEST evaluate different biologic processes and information in brain tumors [ 135 , 136 ]. However, a more recent study from 2020 utilized FET PET-MRI combined with amide-CEST and DSC perfusion to generate intra-lesional hot spot volumes (HSV) in 46 glioma patients [ 137 ]. HSVs generated with amide-CEST in GBM patients were larger than for FET or DSC HSVs.…”
Section: Positron Emission Tomographymentioning
confidence: 99%